Neurotrophin mRNA expression in the central nervous system of the brain stem-spinal cord regenerating model, Anguilla anguilla, the European eel - Peart, Victoria Stephanie (Trinity College (Dublin, Ireland). Department of Zoology, 2007)
Neuronal regeneration is extremely limited in the central nervous system (CNS) of mature amniotes. On the other hand, many anamniotes, such as some fish, display rapid morphological and functional recovery after CNS injury, a process that has often been compared to neuronal development. Neurotrophins are a group of molecules that are crucial in development, as well as in the maintenance and plasticity of the adult nervous system. They are also thought to play an important role in neuronal regeneration. Neurotrophin mRNA and protein are upregulated in the cell bodies and target regions of injured neurons that lie in the mammalian peripheral nervous system (PNS), and which do regenerate after axonal injury. Neurotrophins are also present in the anamniote CNS but little is known about their spatial expression patterns or their involvement in regeneration after neuronal insult in this group of animals. Based on the results of mammalian studies, the hypothesis was formulated that neurotrophin expression may be upregulated in the anamniote CNS after injury in order to aid in neuronal regeneration. To test this hypothesis, neurotrophin and neurotrophin receptor mRNA expression was investigated in the eel CNS at various timepoints before and after spinal cord transection, and during regeneration and functional recovery.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin